Determinants of Fertility in West Sulawesi Province Further Analysis of Indonesia Health Demography Survey Data (IDHS) 2017 - Irma Muslimin; Hadzmawaty Hamzah; Kaprawi Rahman; Sukardi Sukardi; Fajar Akbar (GLOBAL HEALTH SCIENCE GROUP, 2022)
The fertility rate is one of the most decisive demographic factors in reducing the population growth rate in Indonesia. The level of fertility is influenced by several factors, both socio-economic factors and sociodemographic factors. This study aims to look at the determinants of fertility in West Sulawesi. This research was conducted through secondary data analysis from the 2017 Indonesian Health Demographic Survey data. The research sample analyzed was Women of Reproductive Age totaling 1,682. Data were analyzed using the chi square test to see the relationship between the independent variables and the dependent variable that had been determined. The results of the data analysis showed that the age group, education level, place of residence, socioeconomic status, literacy knowledge about the fertile period and use of contraceptives were significantly related to the number of children born alive. Based on the results of this research data analysis, it is necessary to have cross-sector collaboration to improve the socio-economic population, increase the level of education in reducing fertility in West Sulawesi.